Cost utility and budget impact analysis of bortezomib and lenalidomide for the treatment of relapsed/refractory multiple myeloma in the South African public health sector - Matsela, Lineo Marie (Unknown, 2022)
Multiple myeloma (MM) is the second most common haematologic cancer, accounting for approximately 13% of all blood cancer cases worldwide. The global incidence rate increased by 126% from 1990 to 2016. In South Africa, multiple myeloma accounts for approximately 9% of haematological cancers and less than 1% of all cancers. Nevertheless, some studies have reported that the incidence is likely underestimated due to an underdiagnosis of the cancer. Thus, the disease could possibly be an issue of greater concern in South Africa than current statistics indicate. The nature of the MM tumour makes patients prone to resistance of chemotherapy and multiple relapses leading to the development of relapse/refractory multiple myeloma (RRMM). During the relapse/refractory period, the patient is nonresponsive to treatment and/or experiences progressive disease When a patient experiences relapse/refractory MM, their prior, (first line) treatment is readministered if it was clinically efficacious and well-tolerated. Contrarily, a change in regimen is recommended if “an insufficient response, a rapid relapse and poor tolerance” to the first-line treatment is experienced by a patient. Second-line regimens that are recommended due to their proven high clinical efficacy are lenalidomide plus low-dose dexamethasone (LEN/DEX) and bortezomib monotherapy (BORT). The clinical effectiveness of both regimens for second-line treatment of RRMM was reported in the MM009/010 and the APEX studies, respectively, where each regimen was compared against dexamethasone monotherapy. Given this proven clinical effectiveness for RRMM, lenalidomide is under consideration for inclusion in the South African Essential Medicines list. Three treatment strategies for second line RRMM treatment were modelled from a provider's perspective. These strategies were dexamethasone (standard of care), BORT and LEN/DEX. For each strategy we modelled a hypothetical cohort of relapsed/refractory multiple myeloma patients using a three-state Markov model (pre-progression, progression and dead) over a 15-year time horizon. Efficacy data was obtained from the MM009/010 and APEX trials, while utilisation rates were obtained from a European study. Other input data was sourced from local literature. Outcomes were reported in quality adjusted life years (QALYs). Incremental cost effectiveness ratios (ICERs) were calculated for BORT and LEN/DEX and compared to the local cost-effectiveness threshold to determine if the drugs are good value for money for the South African government. The total costs per patient using DEX, BORT and LEN/DEX over 15 years differed significantly resulting in estimates of R8 312.32, R234 995.50 and R1 135 323.37, respectively. The associated health benefits in terms of quality-adjusted life years gained from the treatments were 1.14, 1.49 and 2.29. Hence, for every quality adjusted life year gained from BORT relative to DEX, an additional R654 648.52 would need to be spent. In contrast, when BORT is compared to LEN/DEX, an additional R1 225 542.23 would need to be spent for an additional quality adjusted life year gained from LEN/DEX. Both the BORT and LEN/DEX treatments were not cost-effective relative to the costeffectiveness threshold of R38 500 per DALY gained. Due to the high costs, both BORT and LEN/DEX could potentially have significant economic impacts on the South African public health sector budget. The study suggests that one year of treatment for 337 RRMM patients in South Africa using the BORT and LEN/DEX would increase the budget budget-cost of RRMM treatment by 3136% and 8684%, respectively. Both BORT and LEN/DEX treatments would not be cost-effective strategies for second-line treatment of RRMM in South Africa. The results indicate that the drug prices of lenalidomide and bortezomib hinder the cost-effectiveness of BORT and LEN/DEX. Price reductions could potentially make BORT more cost-effective and allow it to be considered as an option for second-line treatment for RRMM patients.